Numerical study of discrete film cooling near the rudder shaft of a hypersonic air fin model - Dai, Siming; Ma, Haiteng; Xu, Ziran; Feng, Kangjun (Numerical heat transfer. Part A, Applications, 2024)
Rudder shaft, connecting the air fin to the fuselage of hypersonic vehicles through the mounting gap, is subject to intense aerodynamic heating, necessitating thermal protection techniques. Film cooling is a promising technology to mitigate this heating, but its thermal protection performance on the rudder shaft, as well as aerothermal mechanisms behind major design parameters, is still unexploited. This paper conducts numerical simulations to evaluate thermal protection performance of discrete film cooling applied to the rudder shaft of an air fin in hypersonic flow. Three discrete cooling holes are arranged on the flat plate upstream of the rudder shaft. Parametric studies are then executed to investigate the effect of cooling hole locations and coolant injection angles on thermal protection performance of the rudder shaft. k-ω SST model is used to solve the Reynolds-Averaged Navier-Stokes equations, and perfect gas without chemical reaction is adopted. Total pressure of the freestream is set as 0.6 MPa, while that of the coolant is fixed at 12000 Pa. The freestream has a Mach number of 6 and unit Reynolds number is 7.65 × 10 6 /m. It is found that discrete film cooling can provide excellent thermal protection performance on the rudder shaft by consuming a coolant of 1.41 × 10 −4 kg/s. For vertically-injected coolant, thermal protection performance deteriorates as the cooling holes are placed further upstream of the rudder shaft and the distribution of coolant alters qualitatively from a concentrated pattern to a segregated one due to the lower local blowing ratio. If the location of cooling holes is fixed, as the injection angle of coolant decreases, the impingement point of the cooling jet changes from the bottom of air fin to the frontal surface of rudder shaft, and more coolant is attached to the flat plate at the gap bottom.